Kedudukan Kebebasan Akademisi dalam Memberikan Keterangan Ahli pada Perkara Pidana - Fathur Rahman Mustabir; Lisnawaty W. Badu; Suwitno Y. Imran (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
The research focuses on studying the Position of Academic Freedom by academics in providing expert testimony on criminal cases in Indonesia and clarifying the status of lecturers who act as experts. The research method used is normative research method. The emergence of cases of expert witnesses being sued by legal interested parties can undermine the principle of absolute competence of a judicial body. Where in 2018 Dr. Ir Basuki Wasis, M.Sc was sued in a civil lawsuit for expert testimony given in the Corruption Case of the Former Governor of Southeast Sulawesi Province. In the Petitum case number 47/Pdt.G/LH/2018/PN Cbi of the Cibinong District Court that the information given was an unlawful act. even though academics as experts have the second position of evidence regulated in Article 184 of the Criminal Procedure Code. Then a Lecturer who acts as an Expert Witness has Academic Freedom as regulated in article 8 paragraph (1) of Law No. 12 of 2012 concerning Higher Education. The conclusion of the research results obtained is that academics as expert witnesses in Indonesia do not have a clear legal standing because the Criminal Procedure Code and Law No. 12 of 2012 concerning Higher Education do not fully regulate the criteria and requirements for being an expert. Then the phrase "expert witness" is still being debated among academics because it is not specifically stipulated in the law. In contrast to the Netherlands, which determines and regulates expert witnesses specifically, both the criteria and the register of an expert in order to reinforce the position of an expert in the formal law of the Netherlands. However, legal protection for experts has been regulated in several laws and other regulations.